Transforming Social Capital into Economic Capital: An Analysis of PT EAHM's Multi-Level Marketing Strategy for Cahaya Biscuits from the Perspective of Progressive Islamic Marketing - Hasanah, Uswatun; Handriani, Eka (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
This research analyzes the marketing phenomenon of "Biskuit Cahaya,"initiated by PT Ekonomi Aisyiyah Hasanah Makmur (PT EAHM) under theCentral Java 'Aisyiyah Regional Leadership, which presents a uniquebusiness model integrating modern corporate entities with grassrootssocio-religious structures. Utilizing a multidimensional theoreticalframework that synthesizes Social Capital Theory (bonding, bridging, andlinking), Relationship Marketing, and Social Entrepreneurship within theperspective of Progressive Islamic Marketing, this study explores howsocial assets are converted into economic capital through a tiereddistribution network. The findings reveal that while the "bonding" socialcapital among 'Aisyiyah members creates a highly loyal captive marketand reduces conventional marketing costs, the organization faces criticalchallenges regarding the overlap between volunteerism andprofessionalism, as well as logistical inefficiencies. The research suggeststhat the integration of digital transformation through the "Eksys" platformand structured entrepreneurial training for the BUEKA units are essentialto transition from seasonal internal sales to a sustainable national brand.Ultimately, the "Biskuit Cahaya" model proves that utilizing ideologicaltrust and organizational density can drive inclusive economic growth andorganizational independence, serving as a strategic benchmark for faithbasedeconomicmovementsin Indonesia.